Vertical Scope, Turbulence, and the Benefits of Commitment and Flexibility - Claussen, Jörg; Kretschmer, Tobias; Stieglitz, Nils (Management Science, 2015)
We address the contested state of theory and the mixed empirical evidence on the relationship between turbulence and vertical scope by studying how turbulence affects the benefits of commitment from integrated development of components and the benefits of flexibility from sourcing components externally. We show that increasing turbulence first increases but then decreases the relative value of vertical integration. Moderate turbulence reduces the value of flexibility by making supplier selection more difficult and increases the value of commitment by mitigating the status quo bias of integrated structures. Both effects improve the value of integration. Higher levels of turbulence undermine the adaptive benefits of commitment, but have a less adverse effect on flexibility, making nonintegration more attractive. We also show how complexity and uneven rates of turbulence moderate the nonmonotonic relationship between turbulence and integration. This paper was accepted by Jesper Sørensen, organizations.